Multi-step thermal design of microwave vacuum heating to basaltic regolith simulant towards lunar base construction - Kunihiko Kato; Takashi Shirai (Scientific Reports)
Abstract Humanned exploration and extended stay on the Moon are the hottest challenges today. We report highly robust materials by microwave heating under high-vacuum conditions (10− 3 Pa) from a basaltic regolith simulant (FJS-1) to ensure the feasibility of lunar infrastructure construction. The violent degassing dynamics were revealed by monitoring vacuum pressure during heating and analyzing the compounds evolved from basaltic silicate compounds: thermal pyrolysis of silicate compounds became more pronounced above 1000 oC, leading to a catastrophic deformation accompanied by forming countless pores of several hundred µm sizes. The preferential formation of the magnetite phase in vacuum heating dominantly caused the radical change in microwave absorption capacity compared with conventional heating routes using an electrical furnace in atmospheric conditions. Besides, the in-situ measurement of dielectric properties during microwave vacuum heating clarified the increase in one order of magnitude from 100 to 1000 oC. Based on the presumed phenomena during microwave-vacuum heating for basaltic regolith, we propose a new thermal design concept to overcome the practical limitations of microwave technology. The multi-step temperature profile successfully fabricated a highly robust product that demonstrated world-class mechanical performance, equivalent to the compressive strength of 65 MPa without any vigorous hydrostatic cold press as a pre-treatment.